Solving Some Evolution Equations with Mixed Partial Derivatives by Using Laplace Substitution - Variation Iteration Method (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The aim of this paper is to investigate the application of integral transform combined with variation iteration method to solve evolution partial differential equations. The combined form of the Laplace substitution and variation iteration method is implemented efficiently in finding the analytical and numerical solutions of nonlinear evolution partial differential equations with mixed partial derivatives. The obtained solutions are compared to the exact solutions and other existing methods. Illustrative examples show the efficiency and the powerful of the used method.